Ditch 1 from Perdigões within the traditions of Late Prehistoric monumental architecture in the middle Guadiana basin (4th-3rd millennia cal BC) - Márquez-Romero, José Enrique; Mata Vivar, Elena; Jiménez-Jáimez, Víctor José (Universidad de Salamanca, 2018)
Traditional approaches to the Late Prehistory in the middle Guadiana basin (south-western Iberia), have subsumed a variety of site types under a unifying category labelled ‘settlement site’. That included ‘walled enclosures’, ‘ditched enclosures’ and ‘pit sites’. However, they are very different in their form and features, the formation of archaeological deposits and their chronology. This suggests that more fine-tuned analyses, in which the emergence and evolution of every type of site is studied on its own, could be fruitful. In the present paper, ditch 1 from Perdigões (Reguengos de Monsaraz, Portugal) will be put in the wider context of the process of monumentalisation of the middle Guadiana landscapes in the 4th and 3rd millennia cal BC. From the perspective outlined above, we shall make a first attempt to set forth the genealogy of walled enclosures, pit sites and ditched enclosures in the region.
Keywords: Fortificaciones - Historia - Peninsula Ibérica; Península ibérica; Paisaje; Neolítico; Recintos de fosos; Recintos murados; Calcolítico